2009
DOI: 10.1007/s11920-009-0072-3
|View full text |Cite
|
Sign up to set email alerts
|

Mania and mortality: Why the excess cardiovascular risk in bipolar disorder?

Abstract: Individuals with bipolar disorder experience twice the cardiovascular mortality expected from general population estimates. The metabolic syndrome is more common in those with bipolar disorder, with a prevalence ratio of 1.6, and includes many traditional cardiovascular risk factors, which may explain much of the elevated risk. Manic symptom burden also predicts cardiovascular mortality, begging questions regarding other explanations for elevated cardiovascular risk. Ultimately, the mechanisms that lead to ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 58 publications
3
44
1
Order By: Relevance
“…3,4,73,74 Although other processes have also been examined, the sections below highlight inflammation, oxidative stress, and autonomic dysfunction in particular because these arguably have the strongest data thus far.…”
Section: Pathophysiological Processes Bridgingmentioning
confidence: 99%
“…3,4,73,74 Although other processes have also been examined, the sections below highlight inflammation, oxidative stress, and autonomic dysfunction in particular because these arguably have the strongest data thus far.…”
Section: Pathophysiological Processes Bridgingmentioning
confidence: 99%
“…A larger association for bipolar disorder was observed in a similarly designed Swedish study, wherein a SMR of 1.6 was again seen for unipolar major depression though in bipolar disorder this estimate reached 2.2 [6]. The majority of studies that assessed the SMR for both mood diagnoses have found a greater burden of cardiovascular mortality in bipolar disorder compared to unipolar major depression [7]. …”
Section: Vascular Morbidity and Mortality In Mood Disordersmentioning
confidence: 99%
“…However, despite these concerns, antidepressants are frequently employed by physicians that face the complex problems of dealing with bipolar depression (Haeberle et al 2012;Sussman et al 2012). Metabolic abnormalities are common in patients with BD, with a relative risk for metabolic syndrome (MetS) and type 2 diabetes of 1.6-2 in patients with BD compared with the general population (Murray et al 2009;Vancampfort et al 2013Vancampfort et al , 2015a. Patients with BD, especially during depressive phases, are inactive, often eat unhealthy food, smoke more cigarettes (Bly et al 2014;Fagiolini et al 2008;Vancampfort et al 2015b), do not take care of themselves, and do not attend medical checkups (Bradford et al 2008), by all these reasons increasing the risk for metabolic and eventually cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%